Structural and catalytic effects of proline substitution and surface loop deletion in the extended active site of human carbonic anhydrase II. (23rd March 2015) - Boone, Christopher D.; Rasi, Valerio; Tu, Chingkuang; McKenna, Robert
<x xml:space="preserve">Abstract</x> Bioengineering of a thermophilic enzyme starting from a mesophilic scaffold has proven to be a significant challenge, as several stabilizing elements have been proposed to be the foundation of thermal stability, including disulfide bridges, surface loop reduction, ionic pair networks, proline substitutions and aromatic clusters. This study emphasizes the effect of increasing the rigidity of human carbonic anhydrase II (HCA II; EC 4.2.1.1) via incorporation of proline residues at positions 170 and 234, which are located in surface loops that are able to accommodate restrictive main‐chain conformations without rearrangement of the surrounding peptide backbone. Additionally, the effect of the compactness of HCA II was examined by deletion of a surface loop (residues 230–240) that had been previously identified as a possible source of thermal stability for the hyperthermophilic carbonic anhydrase isolated from the bacterium Sulfurihydrogenibium yellowstonense YO3AOP1. Differential scanning calorimetry analysis of these HCA II variants revealed that these structural modifications had a minimum effect on the thermal stability of the enzyme, while kinetic studies showed unexpected effects on the catalytic efficiency and proton transfer rates. X‐ray crystallographic analysis of these HCA II variants showed that the electrostatic potential and configuration of the highly acidic loop (residues 230–240) play an important role in its high catalytic activity. Based on these observations and previous studies, a picture is emerging of the various components within the general structural architecture of HCA II that are key to stability. These elements may provide blueprints for rational thermal stability engineering of other enzymes. Database Structural data have been submitted to the Protein Data Bank under accession numbers 4QK1 (K170P), 4QK2 (E234P) and 4QK3 (Δ230—240).